Acquired right-sided diaphragmatic hernia after pediatric living donor transplantation: a guide for the non-transplant pediatric surgeon - Palmisani, Francesca; Stundner-Ladenhauf, Hannah N.; Pichler, Judith; Aldrian, Denise; Heilos, Andreas; Steinbauer, Philipp; Metzelder, Martin L.; Patsch, Janina M.; Huber, Wolf-Dieter; Oberhuber, Rupert; Krois, Wilfried (Frontiers in Pediatrics, 2025)
BackgroundPediatric living donor liver transplantation (pLDLT) has risen to standard of care for children with liver failure. Strong policies of centralization have led to exceptional results, reducing the risk of morbidity and mortality. As a counterpart, long term follow-up often occurs in centers with no dedicated transplant unit, that should familiarize themselves with the exceptional anatomy of the liver-transplanted child and their unique postoperative complications.MethodsWe reviewed all cases of acquired diaphragmatic hernia (DH) after pLDLT in the period following the establishment of a strong policy of centralization in Austria, between January 2017 and May 2023. All patients were referred for liver transplantation to the newly established national transplant reference center (Medical University of Innsbruck, Austria). Postoperative follow up was conducted either at the transplant center or at their home institutions.ResultsOf the 42 patients which received a pLDLT in the national reference center during the study period, 3 developed an acquired diaphragmatic hernia within the first eight months postoperatively (7%). All patients required emergent surgical treatment in a non-transplant center. All the cases presented with a defect in the posteromedial aspect of the diaphragm, potentially related to thermal effects in the bare area of the diaphragm during transplantation.ConclusionsAcquired diaphragmatic hernia is a rare complication of pLDLT, that mostly occurs in the long-term postoperative follow-up. Accurate knowledge of the surgical site is crucial to assure assessment and management in absence of the transplant-team. With this retrospective analysis we aim to enhance focus on post-liver-transplant complications and offer a guide for the non-transplant pediatric surgeon to raise awareness to post-operative anatomical alterations in these patients.